Examining European Talent Development Environments: Athlete, Parent and Coach Perceptions. Issue 22 (17th November 2022) - Sargent Megicks, Barnaby; Till, Kevin; Rongen, Fieke; Cowburn, Ian; Gledhill, Adam; Mitchell, Thomas; Emmonds, Stacey; Lara-Bercial, Sergio
ABSTRACT: Talent Development Environments (TDEs) aim to provide the appropriate conditions for youth athletes to realise their full sporting potential. How TDEs are designed and operated is therefore of great importance for the development of elite athletes. Stakeholders are vital in this process, yet their perspectives are poorly understood. This study assessed the quality of TDEs across 5 European countries, comparing athlete, parent and coach perceptions. A total of 571 athletes (Mean age = 15.2 ± 1.5 years), 759 parents and 134 coaches were recruited from TDEs across 27 sports. Participants completed the Talent Development Environment Questionnaire-5 or adapted versions. Overall, perceptions of European TDEs were positive. Coaches reported higher perceptions of TDE quality compared to athletes and parents, athletes reported marginally higher perceptions compared to parents. Across stakeholders, Long-Term Development was highest rated, followed by Communication. Support Network was lowest rated. Stakeholder perceptions varied most for the Holistic Quality Preparation subscale, highlighting perceived differences in TDE support for rounded athlete development. From an organisational perspective, identified strengths and weaknesses provide direction to coach and parent education. Practically, TDE leaders should consider how they can refine stakeholder coordination through integrating stakeholder perceptions as valuable feedback into their environment, especially for intangible factors.